2019
DOI: 10.3390/v11121102
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing on Insectivorous Bat Guano: An Accurate Tool to Identify Arthropod Viruses of Potential Agricultural Concern

Abstract: Viruses belonging to the Dicistroviridae family have attracted a great deal of attention from scientists owing to their negative impact on agricultural economics, as well as their recent identification as potential aetiological agents of febrile illness in human patients. On the other hand, some Dicistroviruses are also studied for their potential biopesticide properties. To date, Dicistrovirus characterized in African mainland remain scarce. By using High-Throughput Sequencing technology on insectivorous bat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Previous studies carried out in Zimbabwe included the characterization of Dicistrovirus, Coronavirus and Paramyxovirus in insectivorous bats (Hipposideros caffer) [33,34]. More than 60 bat species have been recorded in Zimbabwe and in rural areas, and people are in close contact with these animals [35], posing a risk of spillover of bat-associated viruses to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies carried out in Zimbabwe included the characterization of Dicistrovirus, Coronavirus and Paramyxovirus in insectivorous bats (Hipposideros caffer) [33,34]. More than 60 bat species have been recorded in Zimbabwe and in rural areas, and people are in close contact with these animals [35], posing a risk of spillover of bat-associated viruses to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Pairwise identity comparisons of this contig sequence with those of representative Picornavirales members indicated that it shares the highest degree of nucleotide identity (71%) with the Darwin bee virus 6 isolate NT-8 (9123 nts) (MG995696), a yet unclassified Picornavirales member reported infecting honey bees (Apis mellifera) [38]. Additionally, the putative proteins, encoded by ORF 1 and ORF 2, share 65.5% and 70% aa identity with Darwin bee virus polyproteins (AWK77846 and AWK77847), supporting its classification as a new species according to the species demarcation criteria proposed by the International Committee on Taxonomy of Viruses (ICTV) (i.e., protein identity of less than 90% with its closest relatives) [39]. The name Hovenia dulcis-associated virus 1 (HDaV1) is proposed for this virus.…”
Section: Resultsmentioning
confidence: 77%
“…SARS-CoV-2 and MERS-Co are among the most notable examples of spillover into humans(Guan et al, 2003). References for arrows: 1 (Bourgarel et al, 2019; Cavanagh and Cavanagh, 2007; Maori et al, 2019; Mcmahon et al, 2018; Moy, 2020; Rizzo et al, 2017) 2: (Miller et al, 2017; Moy, 2020) 3: (Miller et al, 2017; Papineau et al, 2019) 4:(Geisbert et al, 2014; Tao et al, 2020) 5: (Gibbins et al, 2020; Newell et al, 2010; Panon et al, 1988) 6: (Gibbins et al, 2020; Hi, 2020; Katy Askew, 2020)…”
Section: Resultsmentioning
confidence: 99%